Seeing Suffrage : The 1913 Washington Suffrage Parade, Its Pictures, and Its Effects on the American Political Landscape - Stovall, James Glen (Book collections on Project MUSE., 2013)
Although supporters needed seven more frustrating years to ratify the Nineteenth Amendment, the Washington Suffrage Parade of 1913 can, as this book demonstrates, rightly be seen as the moment that forced the public to take seriously the effort to secure the vote for women."--Publisher's website.